Enhancing adoptive cell therapy: future strategies for immune cell radioprotection in neuro-oncology - Abigail J. Groth; Mustafa Khasraw; James D. Byrne; Zachary J. Reitman (npj Precision Oncology)
Abstract Adoptive cell therapy (ACT), particularly chimeric antigen receptor T cell (CAR T) therapy, has emerged as a promising approach in cancer treatment, demonstrating efficacy in hematological malignancies but facing challenges in brain tumors. The combination of ACT with radiation therapy (RT) offers a potential strategy to enhance therapeutic outcomes, as RT can stimulate immune responses by promoting antigen presentation and T cell recruitment. However, a major hurdle is the radiosensitivity of immune cells, leading to their rapid depletion within the radiation field, which undermines the benefits of this combination. This review explores strategies to increase the radioresistance of immune cells, highlighting the need for innovative radioprotective approaches. We discuss the potential of extremophile-derived molecules, such as the Damage Suppressor protein from tardigrades, as novel radioprotectants that could be integrated into ACT protocols. Furthermore, we address key considerations for clinical trial design, including the sequencing of RT and ACT, dosing parameters, and safety considerations. By bridging insights from extremophile biology and immuno-oncology, this work aims to optimize the efficacy of ACT in the challenging context of brain tumors, paving the way for enhanced treatment strategies in neuro-oncology.